Annealing effects on the microstructure of Ge/Si(001) quantum dots - Liao, X; Zou, J; Cockayne, D; Wan, J; Jiang, Z; Jin, G; Wang, K (2001)
Ge/Si(001) multilayer islands produced by gas-source molecular-beam epitaxy at 575 °C were investigated using energy-filtering transmission electron microscopy. Results show, for as-grown samples, not only a continuous enlargement of island size in upper layers but also a continuous increase of Ge concentration within islands in upper layers. As a result of the increasing island size and Ge concentration within the islands, the island density in upper layers decreases. For samples annealed at 900 °C for 5 min, the aspect ratio of buried islands increases significantly, and the average Ge concentration within islands of different layers becomes uniform. © 2001 American Institute of Physics.